Environmental Assessment of the Life Cycle of Bovine Compound Feeds from a Feed Milling Plant in a Large Commercial Farm in Wielkopolska Region, Poland - Jerzy Bieńkowski; Małgorzata Holka (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
In recent years, the importance of environmental threats associated with intensive livestock production has been emphasized. Compound feeds make up a part of the animal production chain. A complete assessment of the animal production system with regard to environmental criteria is therefore impossible without considering the environmental consequences of feed production. The goal of this research is to fill the gap in an environmental assessment of production processes of compound feeds in Poland. The study presents an assessment of production impacts of bovine compound feeds according to Life Cycle Analysis (LCA) methodology. The data for analysis were based on the set of information obtained from the feed milling plant located in a commercial agricultural enterprise in the Wielkopolska region in the years 2015-2016. An inventory table of inputs was prepared in relation to the functional unit of 1 ton of compound feeds and two phases of production processes, i.e. upstream and core. For average compound feed, the impact category indicators for the global warming potential, acidification, eutrophication, photochemical ozone formation, consumption of mineral resources, fossil fuel resources and the emission of the respirable particles were respectively: 605.9 kg CO2 eq, 8.73 kg SO2 eq, 3.32 kg PO4 eq, 0.73 kg ethylene eq, 3.4x10-3 kg antimony eq, 5141.1 MJ and 2.25 kg PM2.5 eq. The upstream phase had the greatest effect on investigated impacts, while the core processes phase had a relatively low impact on environmental threats. It is recommended to broaden the scope of the research for a larger group of feed milling plants with more complex manufacturing processes, with a more branched supply structure and a wide range of compound feeds for different animal types. The obtained data can be a valuable source base in prospective analyses of the life cycle of various animal products in Poland.